The Role of Sharia Fintech Implementation in Overcoming Gharar in E-Commerce Transactions to Ensure Sharia Compliance and Transaction Certainty in the Digital Economy in Indonesia - Reska Maulida; Ahmad Habibi; Muhammad Iqbal Fasa (Best Journal of Administration and Management, 2025)
The study aims to analyze the strategic role of Sharia Fintech implementation in overcoming gharar elements in e-commerce transactions in order to ensure Sharia compliance and increase transaction certainty in Indonesia's digital economy ecosystem. Gharar in e-commerce often occurs due to non-conformity of goods, quality uncertainty, and lack of transparency of information, where buyers cannot physically verify the goods. Using a qualitative descriptive approach through literature studies, it was found that Sharia fintechs offer mitigation solutions through innovations such as Sharia smart contracts that automate clear contracts, Sharia escrow systems that hold funds until goods are received, and blockchain-based halal traceability technology for product transparency. The results of the study show that the adoption of this technology significantly minimizes ambiguity, reduces the risk of disputes, and increases consumer confidence, but the main challenges still include low Sharia digital literacy and not yet optimal integration across e-commerce platforms.